Dropout rate and dropout reasons in talented track and field athletes, a 25 years study - Enoksen, E.; Shalfawi, S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Research explains the early dropout of young talents in sport as a combination of different inner and outer conditions such as individual talent and personal development, athletic progress, motivation, priorities of interest and influence from the social environment (Ames, 1992; Molinero et al., 2006). The aim of the present study was to identify the total dropout rate and dropout reasons in a group of talented track and field athletes from 1975 - 2000. Methods: 202 males and 98 females aged 16 ±2 years took part in this study. The questionnaires designed in 1975 were sent together with informed consent and local ethics committee approval in September 1975 to 320 participants. The questionnaires designed for the 1983 study and the 1989 study were administered in November 1983, and October 1989. All questionnaires were administrated in written form. The participants who did not respond to the first request were sent a new questionnaire two months after, and those who did not answer the second questionnaire were sent a new and last questionnaire after two months from the second questionnaire. Those who did not answer after the third trial were considered as dropped out. In 1989, 10 athletes were chosen for interviews. In 2000, 24 athletes who had continued their athletic career after 1989 were interviewed. The interviews were conducted in the period between September 1989 and October 1989 for the 1989 study, and from February 2000 to November 2000 for the 2000 study. The interviews varied in time from 60 - 120 minutes. Combining the analysis of the quantitative data and qualitative data was to bring forward more refined and valid information about the variables involved in the processes of dropping out from competitive sport at an early age. A chi-square test was administrated to test the difference between males and females dropping out and to test the most significant reasons influencing the athletes` decision to drop out from competing in track and field. Results: The dropout rate was highest when the athletes were 17 years old. Females were clearly dropping out more than males (p < 0.05). Injuries, school demands, and lack of motivation were highly notable reasons to why relatively many athletes dropped out at an early age. Various dropout reasons were important over the life of the study, and differed at the different stages. Conclusion: Today elite sport requires increasingly harder training, tough competitions and constant expectancies of good results. Young talented athlethes who fail to meet these requirements may chose to drop out of competitive sport at an early age.